The Relationship of Self Efficacy with Self Care Management in Hypertension Patients - Putri, Berlian Maharani Febrina; Faqih, Moh. Ubaidillah (Journal of Pubnursing Sciences, 2025)
Background: Self-efficacy in hypertensive patients is crucial in enhancing their confidence to engage in self-care management, thus preventing an increase in morbidity, mortality, and complications arising from hypertension. Aims: To determine the correlation between self-efficacy and self-care management in hypertensive patients. Methods: A descriptive correlational design with a cross-sectional approach was employed in this research. The population of this study consisted of 155 respondents. A cluster sampling technique was used, resulting in a sample size of 112 respondents. A questionnaire was used as the research instrument. Statistical analysis was performed using the Spearman rank test. Results: Analyzed using the Spearman rank test with a significance level of α = <0.05, yielded a p-value of 0.000 and an r-value of 0.556, indicating a strong positive correlation. The findings revealed that nearly all respondents with high self-efficacy had good self-care management (28 respondents, 82.4%), a majority of respondents with moderate self-efficacy had fair self-care management (33 respondents, 63.5%), and half of the respondents with low self-efficacy had fair self-care management (13 respondents, 50.0%). Conclusion: Based on the aforementioned, it can be concluded that self-efficacy is correlated with self-care management in hypertensive patients at Puskesmas Wire, Semanding District. This provides an overview for respondents regarding how self-efficacy can improve self-care management, thereby minimizing the risk of complications.